Dinâmica da conta financeira do balanço de pagamentos dos países emergentes no período 1990-2009: a vulnerabilidade continua - Pereira, Vanessa de Paula (2010)
The main purpose of this study is to analyze the profile of the Financial Account on the emerging economies, more specifically in the cases of Brazil, Argentina, Mexico, Chile, South Korea, Thailand, India and Russia. The goal is to emphasize the high influence of short-term capital in the Balance of Payments in these economies after the financial opening which elevate the vulnerability that the mentioned countries were exposed to. The specific objectives are: i - to raise the international capital flow dynamic towards peripheral countries and ii - to study the volatility of the Financial Account in the studied countries in the following periods 1990-1998, 1999-2002, 2003-2007, 2008-2009. The results of the study show that the more volatile financial account of the Balance of Payments in these countries are Portfolio Flows and Other Financial Flows, not only foreigners but also residents. In the case of Latin American economies, except of the Chilean economy, the more unstable subaccounts are Debt Securities purchased by foreigners, Loans and Financing of foreigners and Currency and Deposits of residents. In the Asian economies it was noticed relevant instability, besides the sub-accounts mentioned previously, in the Equity Securities purchased by foreigners and Other Assets, which also applies in the case of Russia. Moreover, it is important to stress that in India and Russia the sub-accounts only have significant variability in the mid-2000s, when the measures to control capital flows were eased.